AMOJ 2015
DOI: 10.22499/2.6501.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CMIP3 and CMIP5 models over the Australian region to inform confidence in projections

Abstract: Model evaluation is an important tool to help rate confidence in climate model simulations. This can add to the overall confidence assessment for future projections of the Australian climate. Additionally it can highlight significant model deficiencies that may affect the selection of a subset of models for use in impact assessment.Here we present results from an extensive model evaluation undertaken as part of the Natural Resource Management (NRM) Project in order to inform the newest set of climate change pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 96 publications
0
39
0
Order By: Relevance
“…Cross‐model consistency is generally larger for Southeastern Australia, with only a subset of models (CanESM2, CCSM4, CNRM‐CM5, MIROC5, and NorESM1‐M) suggesting a tendency for wetting in any region. Among the models in our full ensemble, only three (MIROC‐ESM‐Chem, MIROC‐ESM, and GISS‐E2‐R) were considered “poor” performers in a recent validation study of the CMIP5 models for Australia [ Moise et al , ].…”
Section: Resultsmentioning
confidence: 99%
“…Cross‐model consistency is generally larger for Southeastern Australia, with only a subset of models (CanESM2, CCSM4, CNRM‐CM5, MIROC5, and NorESM1‐M) suggesting a tendency for wetting in any region. Among the models in our full ensemble, only three (MIROC‐ESM‐Chem, MIROC‐ESM, and GISS‐E2‐R) were considered “poor” performers in a recent validation study of the CMIP5 models for Australia [ Moise et al , ].…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Moise et al . () analysing mean climatologies and precipitations around Australia, ACCESS1.0 was found to be the top scoring model for the full region followed by BCC‐CSM1.1 and EC‐EARTH. Gibson et al .…”
Section: Discussionmentioning
confidence: 97%
“…Other studies following different selection techniques have been developed for this region. In the study by Moise et al (2015) analysing mean climatologies and precipitations around Australia, ACCESS1.0 was found to be the top scoring model for the full region followed by BCC-CSM1.1 and EC-EARTH. Gibson et al (2016b) also found ACCESS1.0 to be the best model over the Australian region, using a synoptic system based on self-organizing maps, although MIRO-C5 was found to be the best using a similar technique in the New Zealand area (Gibson et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the strongest trend is found in the seasons where the largest rainfall decline is projected. It is worth noting that an Australia-wide model evaluation suggested that some models are not able to adequately reproduce the climatology of solar radiation (Moise et al 2015). Globally, CMIP5 models appear to underestimate the observed trends in some regions due to underestimation of aerosol direct radiative forcing and deficient aerosol emission inventories (Allen et al 2013).…”
Section: Changes In the Hydrological Cyclementioning
confidence: 99%